Effect of organic manure, Biofertilizer and foliar spray of Ascorbic acid on vegetative growth and fruit quality of Basheqi cv. of Olive (Olea europaea L.) - Shaymaa Mahfodh Abdulqaderh; Haliz Safar Khalil (Kufa Journal for Agricultural Sciences)
ABSTRACT: This experiment was conducted in a private olive orchard located in the village of Kasara, Dohuk governorate, Kurdistan region, Iraq, during growing season 2021-2022 on 14 years old olive trees cv.  Basheqi (Olea europaea L) planted at 4x8m apart in (silty clay loam) soil, under drip irrigation system. Three levels of Organic manure (poultry manure) at (0, 4 and 8) kg/tree was added to the soil at the second week of December in 2021 season, three levels of Bio-fertilizers (Bio Health) at conc.  (0, 10 and 15) g.l-1 and three concentrations (0, 300 & 600 mg.l-1 ) of foliar spray of  ascorbic acid. Bio-fertilizers and ascorbic acid was carried out two times per season, First: Prior-Flowering, Second: After Setting in order to investigate there influence on growth and Fruit Quality of olive trees. A factorial experiment with three replications was carried out in  a randomized  complete block  design (RCBD), using one tree for each experimental unit. Results indicated that soil application of organic manure (poultry manure) at 8 Kg/tree significantly increased all studied characters {average leaf area, chlorophyll content, Protein % in Leaves, Fruit Total Soluble Solids TSS %, Total Carbohydrates %, Anthocyanin Content, Ascorbic acid (Vit.C), Percentage of Oil}. Soil application of biofertilizer (bio health) at 15g.l-1 significantly increased all study characters except TSS. Foliar application of Ascorbic acid at 600 mg/l-1 significantly increased average leaf area, total chlorophyll content, Protein % in Leaves, Ascorbic acid, Percentage of Oil. In comparison to other interactions, the interaction of (8 kg O.M./tree, 15 g.l-1 bio fertilizer, and 600 mg.l-1 ascorbic acid) appeared to be more efficient in enhancing all characteristics studied in this experiment.